SIMILAR SOUNDING WORDS IN DARI AND ENGLISH, WHICH INDICATE A COMMON ORIGIN OF BOTH THE LANGUAGES - Muslih Ahmad Shikib (American Journals, 2024)
The writing system. Dari uses the Arabic alphabet, English uses the Roman alphabet. Farsi writes from right to left, English from left to right. Farsi doesn’t include short vowel sounds in writing, English does. Farsi spells most words the way they are pronounced. English includes many non-phonetic spellings. Farsi has letters for sounds that exist in English, but English does not have those letters as unique letters (zhe as in genre, ch as in church, sh as in shirt).
Keywords: Sounds, pronounce, structure, unique letters, Dari, Arabic alphabet, phonetic spellings, system.